A combined cooling and power transcritical CO2 cycle for waste heat recovery from gas turbines. (1st September 2022) - Sabzpoushan, S.; Morad, M.R.; Ebrahimi Rahnama, H.
Highlights: A combined cooling and power cycle working with CO2 is proposed for waste heat recovery from a gas turbine. Efficiencies of the combined system and its COP are evaluated for three configurations (simple, split and cascade) versus different cycle parameters. Although the split configuration has the highest net power generation at high and moderate heat source temperatures, in the case of low temperature waste heat from the gas turbine (less than 420 °C), net power of the simple cycle surpasses and the split cycle gives the lowest net power. The split configuration yields the highest thermal efficiency between the three investigated configurations except at low condenser pressures. The split cycle has a slight supremacy in heat recovery efficiency at intermediate and high gas turbine exhaust temperatures. This supremacy persists over all the investigated cycle parameters. For low CO2 mass fractions into the refrigeration part, cascade configuration has the highest COP. For high CO2 mass fractions into the refrigeration part, simple configuration has the highest COP. The split cycle is the most efficient configuration regarding the total system efficiency. Hence, it can be selected as the candidate cycle configuration for further optimization in a future study. Abstract: A transcritical carbon dioxide (T-CO2 ) cycle is analyzed for waste heat recovery from a gas turbine. The cycle is proposed to produce combined power and cooling using carbon dioxide as a single pure working fluid. Simple, cascade and split cycle configurations are compared for power generation using a recuperator while a low-temperature loop is added for the cascade and split cycles. In a previous report in the literature the power generation part alone was presented for the three configurations and it was concluded that the split cycle can produce the highest power among the three systems. Here, the same configurations are studied combined with a compression refrigeration cooling effect with the same working fluid, and a parametric study is conducted. The power cycle is a T-CO2 cycle which absorbs the waste heat from a gas turbine. The effect of different parameters like cooling load, splitters mass fractions, turbine pressure and condenser pressure are investigated and a comparison between the three configurations are demonstrated. It is shown that, for instance, in case of higher temperatures of gas turbine exhaust the split configuration has the highest net power production while using gas turbine exhaust flow of temperatures less than 420 °C the simple configuration produces the maximum output power. From the cooling perspective, for values of turbine inlet pressure higher than 222 bar, abs. the cascade cycle indicates the best cooling performance while the split one takes this position at lower turbine inlet pressures.